2017
DOI: 10.21315/tlsr2017.28.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Intestinal Parasitic Contamination in Select Consumed Local Raw Vegetables and Fruits in Kuantan, Pahang

Abstract: Abstrak: Jangkitan parasit usus adalah salah satu penyakit manusia yang lazimnya menyebabkan masalah kesihatan yang serius dan mengakibatkan isu-isu ekonomi di negara-negara maju dan membangun. Sayur-sayuran mentah dan buah-buahan memainkan peranan yang penting sebagai medium jangkitan parasit ke dalam manusia. Oleh itu, tujuan kajian ini adalah untuk menyiasat pencemaran parasitologi daripada sayur-sayuran berdaun dan buah-buahan yang biasa dimakan serta dipilih penduduk tempatan di Kuantan, Malaysia. Sebanya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
2
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 16 publications
4
22
2
2
Order By: Relevance
“…Elderly individuals who did not regularly practice vegetable washing were 3.19 times more likely to be infected with STHs than those who did wash vegetables. Several studies have reported that consuming unwashed fresh vegetables is a risk factor for STH infection [ 31 , 32 ]. Recently, contamination by STH parasites has been reported in fresh vegetables from southern Thailand, with a contamination rate of 35.1% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elderly individuals who did not regularly practice vegetable washing were 3.19 times more likely to be infected with STHs than those who did wash vegetables. Several studies have reported that consuming unwashed fresh vegetables is a risk factor for STH infection [ 31 , 32 ]. Recently, contamination by STH parasites has been reported in fresh vegetables from southern Thailand, with a contamination rate of 35.1% [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Hamadan, water supplies are provided by the river water, untreated waste water or surface water to be used for irrigation of vegetables cultivated throughout spring and summer, while during autumn and winter, vegetables are imported mostly from the farms of Khuzestan, southwest of Iran, which are irrigated by rain or underground water. Furthermore, increased number of parasites in vegetables during warm seasons might be due to the increase of the temperature intensifying the excretion of parasites by humans or animals (24).…”
Section: Discussionmentioning
confidence: 99%
“…This can be caused by vegetables obtained in dirty physical conditions and not given washing treatment before being sold to the market so that the possibility for contamination is quite large. The conditions in this study are slightly different from those conducted by Rahmati, Fallah, Maghsood, Shamsi-Ehsan, & Matini (2017) and Yusof, et al (2017). In Rahmati, Fallah, Maghsood, Shamsi-Ehsan & Matini research (2017), the most contaminated vegetable is leek.…”
Section: Univariate Results Discussionmentioning
confidence: 73%
“…In a study by Rahmati, Fallah, Maghsood, Shamsi-Ehsan, and Matini (2017), Leeks that are sampled are products that have not been cleaned before being sold. On the other hand, a research by Yusof, et al (2017) discovered gotu kola leaf as the most contaminated vegetable in the Pahang market, Malaysia. This finding is due to the culture of the Pahang community that uses gotu kola leaves daily for cooking purposes Factors that influence the presence of STH in vegetables such as the use of organic fertilizer derived from animal livestock as a medium for fertilizing vegetables (Ravichandran, 2015).…”
Section: Univariate Results Discussionmentioning
confidence: 99%